2020
DOI: 10.17559/tv-20200311150410
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of Centrifugal Vortex Pump Operating Benefits for Energy Efficient Systems

Abstract: One of the ways to improve the performance of centrifugal pumps, proposed and experimentally validated by our research, is the method of creating so-called coherent structures, vortices and turbulence in the peripheral area of the centrifugal stage by adding a vortex rim to the back side of centrifugal rotor. A new construction of the pump, so called centrifugal vortex pump (CV), combines the good sides of these two types of pumps: high head of the vortex pump and high efficiency of the centrifugal pump. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Zhang et al [4] analyzed the hydraulic performance and dynamic characteristics of the centrifugal pump and indicated the pump has better hydraulic behavior when the volute tongue is right in the middle of the two vanes. Mihalic et al [5] improved the performance of a centrifugal pump by adding a vortex rim on the back of the centrifugal rotor, and increased the stability of the pump when pumping a liquid and gas mixture. Shigemitsu et al [6] found that when the centrifugal pump has splitter blades, the flow condition at the rotor outlet becomes uniform, the recirculation zone is suppressed, the volute efficiency is improved, and the vortex loss is reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [4] analyzed the hydraulic performance and dynamic characteristics of the centrifugal pump and indicated the pump has better hydraulic behavior when the volute tongue is right in the middle of the two vanes. Mihalic et al [5] improved the performance of a centrifugal pump by adding a vortex rim on the back of the centrifugal rotor, and increased the stability of the pump when pumping a liquid and gas mixture. Shigemitsu et al [6] found that when the centrifugal pump has splitter blades, the flow condition at the rotor outlet becomes uniform, the recirculation zone is suppressed, the volute efficiency is improved, and the vortex loss is reduced.…”
Section: Introductionmentioning
confidence: 99%